Analisis Sistem Pemerintahan Daerah Dalam Optimalisasi Kinerja Pemerintah Daerah NTT - Githa Asmadeningrum Rosady; Jovita Lituhayu Maheswari; Romadona Putri Pertiwi (Universitas Katolik Widya Karya Malang, 2023)
The changing era has made awareness of democracy and constitutionalism growing rapidly. With these amendments or changes, it is hoped that the 1945 Constitution can become the basic rules of the constitutional system under the conditions of a growing Indonesian state. The constitutional system is defined as the arrangement of elements in the organizational structure of the state that are interrelated. The vast territory of Indonesia requires that the central government hand over some of its authority to local governments. Regional governments specifically have functions, duties, and authorities in managing their own government affairs in their regions. In accordance with their roles and duties, local governments must also be able to handle various cases or problems that could occur unexpectedly, such as an outbreak or corona virus that suddenly attacked the country of Indonesia and resulted in a decrease in people's living standards, especially in the economic, social and law which is also included in the constitutional composition of the Indonesian government. Thus, the central and regional governments in this case have important roles that are interrelated in dealing with problems that occur in Indonesia. This is carried out using the principle of autonomy which is the basic rule of the government in exercising authority in its area. And by using the principle of decentralization, the central government can evenly distribute welfare, quality of life, and progress in infrastructure development in every region in Indonesia.